The Impact of Employee Engagement Programs on Boosting Em-ployee Loyalty and Job Satisfaction in the Garment Industry - Antonius Gulo; Dyah Palupiningtyas (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the effectiveness of the employee engagement program in enhancing employee loyalty and job satisfaction at PT. Sam Sam Jaya Garments. Using a mixed-method approach, the study involved 303 respondents for quantitative data and 15 informants for qualitative data. Data were collected through surveys using the UWES-17, ELS-12, and JSS instruments, as well as in-depth interviews, observations, and document studies. Regression analysis showed that the employee engagement program had a positive and significant impact on employee loyalty (R²=0.587) and job satisfaction (R²=0.642). Qualitative findings revealed career development, two-way communication, reward systems, and work-life balance as key success factors of the program. The implementation of the program successfully reduced turnover from 18% to 12%, increased productivity by 15%, and improved employee satisfaction from 65% to 89%. This study provides a theoretical contribution to the development of an adaptive employee engagement model for the garment industry and a practical contribution in the form of a framework for effective engagement program implementation.